Childhood Albuminuria and Chronic Kidney Disease is Associated with Mortality and End-Stage Renal Disease - Ching-Yuang Lin; Shiuh-Ming Huang (Elsevier, 2016)
We do not yet fully grasp the significance of childhood albuminuria. Based on mass urinary screening (MUS) using albumin-specific dipsticks in school children, we studied the independent association of estimated glomerular filtration rate (eGFR) and albuminuria with mortality and end-stage renal disease (ESRD) in children with chronic kidney disease (CKD). Methods: A prospective cohort of 5351 children with albuminuria detected by school MSU during the period 1992-1996, followed up to 2009. Results: Cumulative mortality rate, prevalence of CKD, and ESRD were higher in children with albuminuria than those without. Albuminuria category was associated with the risk of mortality [hazard ratio (HR) 3.4] and ESRD (HR 3.24). Lower eGFR and albuminuria predicted mortality and ESRD among children with albuminuria and CKD. We found that being below a threshold of 45 mL/min/1.73 m2 was significantly associated with ESRD. The highest renal function decline, along with the steepest slope of cumulative ESRD number, occurred in Stage 3, the critical point in renal progression. Risk factors for renal progression among different age groups with albuminuria were hypercholesterolemia and low serum albumin at 7-17 years of age. Beyond 18 years of age, besides the risk factor, a higher fasting blood sugar (BS) was also noted. Conclusion: Childhood albuminuria is a risk factor for CKD in later life, albuminuria provides additional prognostic information, and complications of CKD should be defined in each case.